2022
DOI: 10.1111/ffe.13822
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial fatigue evaluation of type 316L stainless steel based on critical plane and energy dissipation

Abstract: This paper focuses on a comparative study of the critical plane approach (CPA) and the dissipated energy approach (DEA) for multiaxial fatigue evaluation on an AISI 316L steel. It is a follow-up to our previous study on the development of a DEA model for multiaxial fatigue life prediction. The results demonstrate that the developed DEA model can provide overall better performance compared with some classic CPA models both in terms of prediction accuracy and versatility to multiaxial loading paths. An in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the authors conducted a comparison between the dissipated energy approach (DEA) and the critical plane approach (CPA), 62 including models such as Smith‐Watson‐Topper, 63 Kandil‐Brown‐Miller, 64 and Fatemi‐Socie 65 . The results demonstrated that the developed DEA model not only delivers superior prediction accuracy but also exhibits greater versatility in handling multiaxial loading paths than the traditional CPA models.…”
Section: Fatigue Life Prediction Methodsmentioning
confidence: 99%
“…Furthermore, the authors conducted a comparison between the dissipated energy approach (DEA) and the critical plane approach (CPA), 62 including models such as Smith‐Watson‐Topper, 63 Kandil‐Brown‐Miller, 64 and Fatemi‐Socie 65 . The results demonstrated that the developed DEA model not only delivers superior prediction accuracy but also exhibits greater versatility in handling multiaxial loading paths than the traditional CPA models.…”
Section: Fatigue Life Prediction Methodsmentioning
confidence: 99%
“…Feng et al 30 adopted inherent dissipation as a damage factor to conduct fatigue failure analysis and established a special fatigue life model based on strain energy density dissipation. On the basis of this research, Feng et al 31 compared the critical plane method with the dissipation energy method, established a novel energy model, and finally found that the developed energy model has better prediction effect. Nourian‐Avval and Khonsari 32 put forward a prediction model based on energy dissipation to evaluate fatigue damage by means of taking into account diverse rate of energy dissipation under shear and tensile strain.…”
Section: Introductionmentioning
confidence: 99%
“…Within the same context of fatigue creep interaction, Wang et al 21 proposed a creep-fatigue model using a modified model based on the dissipated strain energy per unit volume and applied it to a number of steel alloys with satisfactory results. An evaluation of the dissipated energy approach for AISI 316L alloy under multiaxial fatigue was carried out by Feng et al 22 and showed that, overall, it was superior to models based on the critical plane approach.…”
Section: Introductionmentioning
confidence: 99%